ANALISIS PERMINTAAN DEPOSITO DALAM VALUTA ASING PADA BANK SWASTA NASIONAL DI INDONESIA - Siti Fatimah Nurhayati; Kurniawati Niladewi (Muhammadiyah University Press, 2003)
High demand for foreign currency deposit is the background of this research with purpose to analyze influence Gross Domestic Product (GDP) per capita, Rupiah deposit interest rate, exchange rate Rupiah to America Dollar, and London Interbank Offer Rate (LIBOR) international interest rate for deposit demand in foreign currency in National Private Bank in Indonesia. To analyze that influence quadratic linear regression analysis used with Partial Adjustment Methods (PAM). From classic assumption test, there's no multicollinearity, heteroscedasticity, and autocorrelation. From statistical test resulted (test-t) that foreign currency savings from previous period, Rupiah deposit interest rate and LIBOR international interest rate have effect to deposit demand in foreign currency, with different validity rate such as: a = 1%, a 5% and a = 10%, meanwhile GDP per capita and exchange rate have no affect to deposit demand in foreign currency. F-Test result that with validity level 99%, independent variables concurrently have effect to dependent variable. R2 result shows that 98% variance foreign currency deposit effect can be explained by variance in model, the other 2% explained by other variable excluded from applied model. However, long term adjustment value (d) amount